Evaluation of lipid matrix microencapsulation for intestinal delivery of thymol in weaned pigs. Issue 1 (22nd November 2019) - Choi, Janghan; Wang, Lucy; Ammeter, Emily; Lahaye, Ludovic; Liu, Song; Nyachoti, Martin; Yang, Chengbo
Abstract: Essential oils (EO) are defined as plant-derived natural bioactive compounds, which can have positive effects on animal growth and health due to their antimicrobial and antioxidative properties. However, EO are volatile, can evaporate quickly, and be rapidly absorbed in the upper gastrointestinal tract. Also, due to their labile nature, the stability of EO during feed processing is often questionable, leading to variations in the final concentration in feed. Encapsulation has become one of the most popular methods of stabilizing EO during feed processing, storage, and delivery into the lower gut. The objectives of the present study were to 1) evaluate the stability of thymol microencapsulated in combination with organic acids in commercially available lipid matrix microparticles during the feed pelleting process and storage; 2) validate and demonstrate the slow release of thymol from the lipid matrix microparticles in a simulated pig gastric fluid (SGF) and a simulated pig intestinal fluid (SIF); and 3) evaluate in vivo release of thymol from the lipid matrix microparticles along the pig gut. The results showed that thymol concentration was not significantly different in the mash and pelleted feeds ( P > 0.05). In the in vitro study, 26.04% thymol was released in SGF, and the rest of the thymol was progressively released in SIF until completion, which was achieved by 24 h. The in vivo study showed that 15.5% of thymol was released in the stomach, and 41.85% of thymol was delivered in the mid-jejunum section. Only 2.21% of thymol was recovered in feces. In conclusion, the lipid matrix microparticles were able to maintain the stability of thymol during a feed pelleting process and storage and allow a slow and progressive intestinal release of thymol in weaned pigs.